Measurement and modelling of the solubility of dodecylcyclohexane in supercritical carbon dioxide. (22nd June 2020) - Yang, Xin; Xiang, Shuo; Su, Peng; He, Yan; Liu, Ping; Chen, Ligong
In developing the application of using supercritical carbon dioxide (sc-CO2 ) to extract fresh base oil from waste lubricant oil, the equilibrium solubility data is very valuable. In this study, the equilibrium solubilities for one of the single lubricant oil component, dodecylcyclohexane, were determined in the temperature T = 313.2 K, 328.2 K, 343.2 K, 358.2 K, 373 K and at pressures up to 17.76 MPa. Phase equilibrium solubility measurements were made in a high-pressure visual cell with variable volume, based on the static-analytic method. Oil solubility is strongly dependent on the density of carbon dioxide (CO2 ), which increased with pressure at constant temperature while decreased with temperature at same pressure. The solubility data were correlated using three density-based models: Mendez-Santiago and Teja (MST) equation, del Valle and Aguilera equation, Adachi and Lu equation, the results showed that all of these models can represent the experimental data well. Since the Adachi and Lu model provided the best regression analysis ( R 2 ) and the lowest average absolute relative deviation (AARD) than the other two models in the examined experimental range, indicating the nonlinear equation of Adachi and Lu model best agreement with the experimental data.